Music-based neurofeedback system for stress regulation and memory stimulation - Bocanegra Pérez, Álvaro J.; Velásquez Pérez, José L.; Martínez Díaz, Valentina; Cárdenas Poveda, Carolina; Rizo Arévalo, Alejandra; López López, Juan Manuel (The International Society For Optical Engineering, 2020)
Although musical neurofeedback is used in multiple works, few systems have been developed for stress regulation, and no systems have been developed for memory stimulation. For this reason, a music-based neurofeedback system for stress regulation and memory stimulation is proposed. This system was designed as a response to a previous research called “Neurophysiology of Emotions and Intimate Partner Violence (IPV) against Women”. The designed system uses 8 EEG channels to analyze alpha and theta brain-waves from 4 areas of the brain: prefrontal, frontal, temporal and central. By recording a 30 seconds baseline, the system is capable to detect changes in the EEG signal that can be used for the interaction. For feedback, three musical features are modified depending on the EEG analysis: tempo, loudness and loudness of the voice of the singer. For testing the system, two protocols were designed, these protocols focused on memory stimulation and stress regulation. They were designed specifically for each one of the three types of feedback. These protocols were applied on two women (43 and 52 years old), both had been part of the previous project. Results are promising, showing changes in the EEG signals of the participants when comparing the first session and the last one. Changes in performance of some specific tasks in the protocols, show an adequate usability of the system. Further studies will be carry on in order to evaluate long-term effects of the system with more activities.

Aunque el neurofeedback musical se utiliza en múltiples trabajos, se han desarrollado pocos sistemas para la regulación del estrés, y no se han desarrollado sistemas para estimular la memoria. Por este motivo, un neurofeedback basado en música Se propone un sistema para la regulación del estrés y la estimulación de la memoria. Este sistema fue diseñado como respuesta a una investigación previa denominada “Neurofisiología de las emociones y violencia de pareja (IPV) contra las mujeres”. El sistema diseñado utiliza 8 canales EEG para analizar ondas cerebrales alfa y theta de 4 áreas del cerebro: prefrontal, frontal, temporal y central. Al registrar una línea base de 30 segundos, el sistema es capaz de detectar cambios en la señal EEG que se pueden utilizar para la interacción. Para retroalimentación, se modifican tres características musicales. Dependiendo del análisis EEG: tempo, sonoridad y sonoridad de la voz del cantante. Para probar el sistema se diseñaron dos protocolos, estos protocolos se centraron en la estimulación de la memoria y regulación del estrés. Fueron diseñados específicamente para cada uno de los tres tipos de retroalimentación. Estos protocolos Se aplicaron a dos mujeres (43 y 52 años), ambas habían sido parte del proyecto anterior. Los resultados son prometedores y muestran cambios en las señales EEG de los participantes al comparar la primera sesión y la última. Los cambios en el desempeño de algunas tareas específicas en los protocolos, muestran una adecuada usabilidad del sistema. Se llevarán a cabo más estudios para evaluar los efectos a largo plazo del sistema con más actividades.
Keywords: Memoria - Aspectos fisiológicos; Memory - Physiological aspects; Estrés (Fisiología); Stress (Physiology); Aparatos fisiológicos; Physiological apparatus; Electroencefalografía; Electroencephalography; Memoria; Memory; Música; Music; Neurofeedback; Estrés; Stress